2008 5th IEEE Consumer Communications and Networking Conference 2008
DOI: 10.1109/ccnc08.2007.219
|View full text |Cite
|
Sign up to set email alerts
|

WEIRD - Real Use Cases and Applications for the WiMAX Technology

Abstract: -IEEE 802.16/WiMAX is one of the most promising technologies for Broadband Wireless Access, both for fixed and mobile use. This paper presents the structure of some testbeds, set up in the framework of the European project WEIRD, about novel applications running on top of a WiMAX-based end-to-end architecture. The presented testbeds are based on real use case scenarios, including monitoring of impervious areas, telemedicine and tele-hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
3
0
4
Order By: Relevance
“…The WEIRD system design ( Figure 2) was based on state-of-theart technologies and ongoing standardization processes and aims to be a part of a full multidomain network architecture, allowing fixed and mobile access. Designed to offer solutions not only for volcano monitoring but also for other emergency scenarios like fire prevention and tele-medicine (Mignanti et al 2008), the WEIRD system aims to enhance WiMAX technology. It takes into account the guidelines of IEEE 802.16d, IEEE 802.16e, and WiMAX Forum (WiMAX Forum 2009) but adds important features, especially with respect to end-toend control plane and QoS resource control and management.…”
Section: The Weird Systemmentioning
confidence: 99%
“…The WEIRD system design ( Figure 2) was based on state-of-theart technologies and ongoing standardization processes and aims to be a part of a full multidomain network architecture, allowing fixed and mobile access. Designed to offer solutions not only for volcano monitoring but also for other emergency scenarios like fire prevention and tele-medicine (Mignanti et al 2008), the WEIRD system aims to enhance WiMAX technology. It takes into account the guidelines of IEEE 802.16d, IEEE 802.16e, and WiMAX Forum (WiMAX Forum 2009) but adds important features, especially with respect to end-toend control plane and QoS resource control and management.…”
Section: The Weird Systemmentioning
confidence: 99%
“…Several research works and projects have demonstrated that WiMAX is a good candidate, among the existing wireless networks and notably Wi-Fi which is the reference industrial model, to support audio broadcasting [3][4][5][6][7]. While [3] and [4] are particularly focused on QoS (Quality of Service) support and improvements, [5,6,7] are focused on performance evaluation of resource allocation mechanisms and mobile access.…”
mentioning
confidence: 98%
“…While [3] and [4] are particularly focused on QoS (Quality of Service) support and improvements, [5,6,7] are focused on performance evaluation of resource allocation mechanisms and mobile access.…”
mentioning
confidence: 99%
“…É importante ressaltar que fotodiodos do tipo avalanche (Avalanche Photodiode -APD) não são aplicados em sistemas RoF devido ao grande ruído gerado durante o processo de fotodetecção, o que pode distorcer o sinal, afetando o desempenho do sistema de comunicação. Sistemas RoF podem ser aplicados em soluções de última milha, expansão da área de cobertura, redução de regiões de sombra, distribuição de sinais Wi-Fi em ambientes indoor e outdoor [17,18,23], interconexão de ERBs e na distribuição de internet banda larga sem-fio [17,[25][26][27][28][29], figura 2.2.…”
Section: Arquitetura E Aplicaçõesunclassified
“…Algumas aplicações da tecnologia RoF incluem a implementação de redes de sensores sem-fio [23], distribuição de redes Wi-Fi em ambientes indoor e outdoor [24], redes WiMAX [25][26][27][28][29] e radioastronomia [30][31][32]. Entretanto, a área que mais movimenta o mercado de sistemas RoF é a de telefonia móvel com freqüências de até 6 GHz.…”
Section: Introductionunclassified